2017
DOI: 10.1016/j.conbuildmat.2017.04.154
|View full text |Cite
|
Sign up to set email alerts
|

An overview on the effect of internal curing on shrinkage of high performance cement-based materials

Abstract: High performance cement-based materials, such as high or ultra-high performance concrete (HPC or UHPC) have been widely used and still faces the risk of cracking caused by shrinkages, especially autogenous shrinkage. Internal curing is an effective method to reduce or even eliminate autogenous shrinkage and has effects on chemical shrinkage, dry shrinkage, etc. The commonly used internal curing materials include super-absorbent polymer (SAP) and porous materials. Porous materials refer to lightweight aggregate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 195 publications
(74 citation statements)
references
References 73 publications
(110 reference statements)
3
68
1
2
Order By: Relevance
“…Calculated values of both factors for tested SFRCs are graphically presented in Figure 5. Equations (11) and (12) describe relations visible in Figure 5. It can be easily observed that all tested SFRCs fulfill both requirements, thus reinforcement substitution is enabled in all analyzed cases.…”
Section: Discussionmentioning
confidence: 99%
“…Calculated values of both factors for tested SFRCs are graphically presented in Figure 5. Equations (11) and (12) describe relations visible in Figure 5. It can be easily observed that all tested SFRCs fulfill both requirements, thus reinforcement substitution is enabled in all analyzed cases.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical shrinkage is recognised as one of the main causes of early-age autogenous shrinkage resulting from volumetric difference between chemical reactants and products in matrix. The previous studies of chemical shrinkage in OPC system reported that the inclusion of SAP increased chemical shrinkage since the additional water promoted further hydration [18]. Thus, more capillary voids were formed, which contributed to a greater shrinkage.…”
Section: Chemical Shrinkagementioning
confidence: 94%
“…In general, various curing methods including external and internal curing are applied to reduce shrinkage of concrete by maintaining the relative humidity. The internal curing method has better effects by adding materials with a high water absorption capacity, which can gradually release water during concrete hardening, such that additional water is supplied to the surrounding matrix once self-desiccation occurs, which can then eliminate shrinkage and stimulate further reaction [18][19][20][21]. Lightweight aggregate and superabsorbent polymer (SAP) have been commonly used as internal curing agents in previous research on internal curing of concrete.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations